Outcomes for Patients with Residual Stage II/III Breast Cancer Following Neoadjuvant Chemotherapy (AFT-01) - Stankowski-Drengler, TJ (Ann Surg Oncol, 2020)
INTRODUCTION: Pathologic complete response (pCR) after neoadjuvant chemotherapy has a demonstrated survival advantage; however, outcomes for non-pCR by receptor status are less understood. We sought to evaluate survival and distant recurrence by receptor status for patients with residual stage II/III breast cancer. METHODS: A stage-stratified random sample of 11,366 patients with stage II-III breast cancer in 2006–2007 was selected from 1217 facilities in the National Cancer Database for a Commission on Cancer Special Study. We identified patients with residual pathologic stage II/III cancer who received standard of care therapy based on receptor status. Distant recurrence and 5-year survival were abstracted and Kaplan-Meier curves were generated by receptor status. Multivariable Cox regression was used to estimate hazard ratios for death and distant recurrence. RESULTS: 734 patients had residual disease; 58%, 28%, and 14% were ER or PR+/Her2neu−, ER and PR−/Her2neu−, and Her2neu+(any ER/PR) respectively. ER and PR−/Her2neu− cancers had the poorest 5-year overall (52% vs 82% for Her2neu+ and ER or PR+/Her2neu−, p<0.0001) and distant recurrence-free survival (57% vs 72% Her2neu+ and 77% ER or PR+/Her2neu, p<0.0001). Cox regression models demonstrated a higher likelihood of distant recurrence and death for patients with ER and PR−/Her2neu− disease (HR 2.25, 95% CI 1.56–3.24 and HR 3.19, 95% CI 2.20–4.64 respectively) compared to ER or PR+/Her2neu−. CONCLUSION: Patients with residual ER and PR−/Her2neu− cancer have a significant risk of distant recurrence and mortality compared to other breast cancer types, supporting the consideration for additional adjuvant therapy and novel clinical trials in this cohort.